Gas-phase redox dynamics in high-energy collisions - Nielsen, Anders (2009)
Mass analysed ion kinetic energy (MIKE) spectra following collisions have been recorded using a double focusing mass spectrometer with 5 kV acceleration voltage. Metal complexes studied were formed by pick-up of metal atoms in mixed argon/solvent clusters made by supersonic expansion. DFT calculations were used to rationalise experimental data.